Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode RGEC di PT Bank Mandiri Taspen KCP Ujung Berung - Kamelia, Deska; Nur'aeni, Nur'aeni; Nuraeni, Eni (Jurnal Dimamu, 2024)
Based on the observation results, this study is motivated by the fluctuations in the health ratio of PT Bank Mandiri Taspen from 2019 to 2023. This study aims to analyze the health level of PT Bank Mandiri Taspen using the RGEC method. This method consists of four evaluation factors: Risk Profile, Good Corporate Governance (GCG), Earning, and Capital. This study is a quantitative descriptive study using secondary data obtained from PT Bank Mandiri Taspen's annual financial reports and governance reports from 2019 to 2023, which have been published regularly. The results of this study show that the health level of PT Bank Mandiri Taspen from 2019 to 2023, measured using the RGEC method based on the Risk Profile factor, which is evaluated by the NPL and LDR ratios, obtained a healthy rating with a score of 2.1. The Good Corporate Governance factor obtained a healthy rating with a score of 2. The Earning factor, evaluated by the ROA, ROE, BOPO, and NIM ratios, obtained an extremely healthy rating with a score of 1.3. The Capital factor, evaluated by the CAR ratio, obtained an extremely healthy rating with a score of 1.